2020
DOI: 10.3390/ijerph17249439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multi-Modal Therapies for Kinesiophobia Caused by Musculoskeletal Disorders: A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis aimed to identify the effect of multi-modal therapies that combined physical and psychological therapies for kinesiophobia caused by musculoskeletal disorders compared with uni-modal therapy of only phycological therapy or psychological therapy. The search terms and their logical connector were as following: (1) “kinesiophobia” at the title or abstract; and (2) “randomized” OR “randomized” at title or abstract; not (3) ”design” OR “protocol” at the title. They were type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
(75 reference statements)
1
17
0
Order By: Relevance
“…Fear of movement may contribute to decreased muscular strength, increased postural sway, and impaired proprioception in musculoskeletal disorders [ 22 , 23 , 24 ]. Kinesiophobia can significantly impact ankle JPS and postural control, and these factors should be considered while rehabilitating patients with FAI to achieve a favorable and positive outcome [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fear of movement may contribute to decreased muscular strength, increased postural sway, and impaired proprioception in musculoskeletal disorders [ 22 , 23 , 24 ]. Kinesiophobia can significantly impact ankle JPS and postural control, and these factors should be considered while rehabilitating patients with FAI to achieve a favorable and positive outcome [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result could be supported by high-level clinical evidence. Apart from the systematic and meta-analysis mentioned in the introduction section of this review (Xu et al, 2020 ), many randomized controlled trials concluded a similar result to support the clinical practice of multi-disciplinary interventions for kinesiophobia caused by musculoskeletal pain. For example, a pragmatic randomized controlled trial conducted in 2020 claimed that a multi-model treatment protocol combined with nature activity therapy and usual care could be an effective co-adjuvant multicomponent treatment for improving fibromyalgia-related symptoms (Serrat et al, 2020 ), and another randomized controlled trial conducted in 2013 demonstrated that a long-term multidisciplinary treatment program was superior to the exercise program in reducing disability, fear-avoidance beliefs and pain, as well as enhancing the quality of life of patients with chronic low back pain.…”
Section: Discussionmentioning
confidence: 65%
“…However, since most of the treatment protocols for musculoskeletal disorders are mainly focused on the injured tissues, aiming to restore the physiological functional integrity of damaged tissues, the TSK scores were usually reported as a secondary outcome, and there was a limited number of studies that focus on the treatments for kinesiophobia (Lara-Palomo et al, 2013 ; Monticone et al, 2017 ; Sarig Bahat et al, 2018 ). A systematic review and meta-analysis published in 2020, which only included randomized controlled trials that used the TSK-17 as outcome measures, identified the effect of multi-modal protocols that combined physical and psychological therapies for kinesiophobia caused by musculoskeletal disorders compared with uni-modal therapy of only phycological therapy or psychological therapy, demonstrating that, despite a large heterogeneity within studies, multi-modal protocols might be more effective in reducing kinesiophobia than the unimodal of only physical or psychological therapy (Xu et al, 2020 ). Therefore, a further review of studies in which more versions of TSK were used as outcome measures should be made to create more comprehensive, high-quality, and low-bias clinical evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Workers who suffer from this disorder may experience severe pain, which is reflected in a decrease in productivity and quality of work, and can even cause disability, which causes absenteeism from work and leads to increased costs for businesses and for the public health system [ 2 ]. Pain caused by musculoskeletal disorders is the second leading cause of disability [ 6 ], and, according to the International Labour Organization (ILO), it is estimated that occupational accidents and diseases cause the loss of 4% of the gross domestic product (GDP), or about $2.8 billion in direct and indirect costs.…”
Section: Introductionmentioning
confidence: 99%